Executives' short-term and long-term incentives - a distributional analysis - Michael Haylock (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
Executives are often paid for short-term changes in shareholder wealth, but rational shareholders want executives to maximize long-term shareholder wealth. Incentives for short-term and long-term oriented behavior may depend on an executive's level of pay in the distribution, holding other factors constant. This paper tests for distributional heterogeneity of short-term and long-term incentives in a 12 year cross-country panel of executives. I use the band-pass filter to separate short-term and long-term shareholder wealth changes (Christiano and Fitzgerald, 2003), and estimate of the shareholder wealth-pay relation using method of moments-quantile regression, developed by Machado and Santos Silva (2019), which accounts for time-constant unobserved heterogeneity of executive-firm pairs across the distribution. When using yearly total compensation to measure pay, executives in the upper tail of the conditional compensation distribution have longer-term oriented incentives. In contrast, when accumulated executive wealth is used to measure pay, executives in the upper tail of the wealth distribution have shorter-term oriented incentives. Since executive wealth encompasses changes to executive utility after pay is granted through accumulated equity-linked pay, it is the preferred measure for evaluating equity-linked pay. Results thus suggest that equity-linked pay should have a longer vesting period for executives in the upper tail than in the lower tail. I find evidence that executives in the upper-tail are evaluated relatively to the industry's short-run and long-run performance.
urn:nbn:de:bsz:21-dspace-983372
Keywords: J31; M12; M52; 330; Executive Compensation; Method of Moments-Quantile Regression; Short-Term Performance; Long-Term Performance; Distribution; Benchmarking